1999
DOI: 10.1023/a:1018849029727
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: SLex-CMPul was found to have the potential to target drugs to the inflammatory lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…3) On the other hand, in these studies, we unexpectedly found that a significant amount of 2-3SLe x -CMPul was sequestered by the spleen but not CMPul, Neu5Ac-and SLN-CMPul. 5) Diethylaminoethyldextran 6) and dextran grafted onto poly-L-lysine 7) have already been reported to be preferentially taken up by the spleen and lymph nodes, but their amount in the spleen were much less than that of x -CMPul.…”
mentioning
confidence: 69%
See 4 more Smart Citations
“…3) On the other hand, in these studies, we unexpectedly found that a significant amount of 2-3SLe x -CMPul was sequestered by the spleen but not CMPul, Neu5Ac-and SLN-CMPul. 5) Diethylaminoethyldextran 6) and dextran grafted onto poly-L-lysine 7) have already been reported to be preferentially taken up by the spleen and lymph nodes, but their amount in the spleen were much less than that of x -CMPul.…”
mentioning
confidence: 69%
“…x moiety in 2-3SLe x -CMPul was recognized by E-selectin 3) and the fucose and 2-3 linked sialic acid that are essential sugar residues for binding to selectins were structurally required for the accumulation in the peripheral lymphoid tissues. 2) However, E-and P-selectins are not thought to be constitutively expressed in normal spleen and lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations